Analysis Of Factors Of Occupational Fatigue In Outpatient Nurses At Siaga Medika Hospital, Banyumas - Heriyono, Muhamad; Khotimah, Khusnul; Trisnawati, Yuli; Imelida, Gracia Pricillia (Program Studi Sarjana Kesehatan Masyarakat Universitas Prima Indonesia, 2025)
One factor that can cause workplace accidents is work fatigue. In addition to reducing productivity, work fatigue can also complicate tasks. This study aims to determine the characteristics of participants and determine the factors influencing work fatigue among outpatient nurses at Siaga Medika Banyumas Hospital in 2023. This study used a case study approach with qualitative methodology. The research sample consisted of five people selected using a purposive sampling strategy. Primary and secondary data were obtained through interviews using the Nur Indah Rintonga questionnaire in 2016 and supported by a grounded theory data analysis methodology. The findings of this study are presented in the form of respondent characteristics, namely the identities of respondents who work as three orthopedic nurses and two internal medicine nurses. Age and health conditions are examples of internal factors influencing work fatigue, while workload is an example of an external factor. Based on the feelings of fatigue experienced by respondents, 3 out of 5 respondents said they often felt work fatigue, while the other 2 only occasionally. Based on the interview results, all respondents confirmed that the main cause of their fatigue was due to excessive workload, supported by factors such as age and health status. Based on the results of the research conducted, it is recommended that the work organizer, namely the hospital, re-evaluate the real workload in the field by implementing work policies in the hospital. Kata kunci : kelelahan kerja, umur, status kesehatan, beban kerja